2014
DOI: 10.1073/pnas.1324184111
|View full text |Cite
|
Sign up to set email alerts
|

Detecting grain rotation at the nanoscale

Abstract: Significance The plastic deformation of nanomaterials has long been wrapped in mystery. Grain rotation is suggested to be a dominant mechanism of plastic deformation for ultrafine nanomaterials. However, the in situ observation of grain rotation has been made possible only for coarse-grained materials. Here we report the in situ high-pressure detection of grain rotation at the nanoscale. The surprising observation is that the texture strength of the same-sized platinum drops rapidly with decreasing g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 28 publications
(45 reference statements)
4
41
0
Order By: Relevance
“…In particular, both dissipated energy (the stress-strain hysteresis loop area D) and the temperature dependence of phase transition stress ( dT d /  ) decrease rapidly with GS, and cyclic stability is enhanced significantly with GS reduction. It is shown that such significant GS effects is primarily caused by the gradual dominance of interfacial energy terms (of grain boundary and phase boundary) in the energetics of the polycrystalline system [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, both dissipated energy (the stress-strain hysteresis loop area D) and the temperature dependence of phase transition stress ( dT d /  ) decrease rapidly with GS, and cyclic stability is enhanced significantly with GS reduction. It is shown that such significant GS effects is primarily caused by the gradual dominance of interfacial energy terms (of grain boundary and phase boundary) in the energetics of the polycrystalline system [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…However, the grain rotation mechanism remains elusive because several processes such as curvature-driven GB migration, lattice diffusion, dislocations, and disclinations may play roles that complicate investigations on the grain rotation mechanisms [17][18][19]. Based on the Read-Shockley model, the conventional belief is that GB-mediated mechanisms dominate the plastic deformation of nanomaterials, resulting in an enhancement in the grain rotation activity of fine nanocrystals [20][21][22][23], i.e. smaller grains rotate more under stress [4,15,24].…”
mentioning
confidence: 99%
“…This plateau is then followed by a decrease at pressures higher than ≈50 GPa, indicating a strain softening phenomenon. This may due to the grain boundary sliding or grain rotation at such high pressures . Alternatively, the stress may be released through a new slip system enabled by pressure‐induced bond rearrangement, a phenomenon previously observed by our group for WB 4 .…”
Section: Resultsmentioning
confidence: 99%